Global climate change and Macadamia habitat suitability: MaxEnt-based prediction under future scenarios - Li, Yifan; Zhong, Tao; Ning, Ya; Chen, Yuchun; Yang, Tingmei; Yue, Hai; Yang, Yaowen; Zhao, Hong; Wu, Haibin; Jin, Zhaoqiang; Liu, Jin (Frontiers in Plant Science, 2025)
Global climate change poses a major challenge for contemporary forestry. Macadamia is an economically valuable tree genus that is widely cultivated across multiple countries and regions. However, few studies have focused on its adaptive distribution and spatiotemporal dynamics under projected global warming scenarios. In this study, we collected the global occurrence records of two commercial Macadamia species (Macadamia integrifolia Maiden & Betche and Macadamia tetraphylla L.A.S. Johnson) and employed a parameter-optimized MaxEnt model to project their suitable habitats under current and future climate scenarios. The optimized model exhibited excellent predictive performance (AUC = 0.979), with a regularization multiplier of 0.5 and linear–quadratic–hinge feature combination. Key bioclimatic variables include: annual Mean temperature (bio1), isothermality (bio3), min temperature of coldest month (bio6), annual precipitation (bio12), and precipitation of driest month (bio14), which collectively comprise 88.2% of the model’s explanatory power. Under the current scenario, the most suitable cultivation areas were determined to be located in Australia, China, South Africa, Brazil, Madagascar, Argentina, and the United States. Compared with the current scenario, total habitat areas under future scenarios (specifically SSP126/585 in the 2030s and 2050s; SSP126/245/370 in the 2070s) are projected to increase by 1.13–7.51%, while reductions of 0.03–2.98% are projected under the other scenarios (SSP245/370 in the 2030s and 2050s; SSP585 in the 2070s). Notably, Brazil exhibits habitat reductions of 2.59–20.06% across all scenarios, while China shows increases of 0.70–45.11%. Furthermore, M. integrifolia was determined to exhibit greater cultivation potential and global expansion feasibility in range than M. tetraphylla. This study elucidates the dominant environmental drivers, current habitat suitability, and climate-driven shifts in Macadamia distribution, providing an empirical basis for sustainable cultivation under climate change.